1999
DOI: 10.1021/jm990341r
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore/Receptor Models for GABAA/BzR Subtypes (α1β3γ2, α5β3γ2, and α6β3γ2) via a Comprehensive Ligand-Mapping Approach

Abstract: Pharmacophore/receptor models for three recombinant GABA(A)/BzR subtypes (alpha1beta3gamma2, alpha5beta3gamma2, and alpha6beta3gamma2) have been established via an SAR ligand-mapping approach. This study was based on the affinities of 151 BzR ligands at five distinct (alpha1-3,5,6beta3gamma2) recombinant GABA(A)/BzR receptor subtypes from at least nine different structural families. Examination of the included volumes of the alpha1-, alpha5-, and alpha6-containing subtypes indicated that region L(2) for the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
181
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(188 citation statements)
references
References 127 publications
(458 reference statements)
7
181
0
Order By: Relevance
“…In addition, substitution for flumazenil occurs with other drugs that antagonize diazepam at BZ receptors [e.g., Ro 14-4513] or that functionally antagonize diazepam at other sites on the GABA A receptor complex (e.g., pentylenetetrazol; Gerak and France, 1999). The similar although not identical binding profile of ␤-CCt and flumazenil at BZ receptors suggests that ␤-CCt antagonizes chronic diazepam at BZ receptors to precipitate withdrawal (Huang et al, 2000). ␤-CCt is approximately 100-fold less potent than flumazenil in diazepam-treated monkeys, a difference com- parable with that observed in untreated monkeys (see below; Paronis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, substitution for flumazenil occurs with other drugs that antagonize diazepam at BZ receptors [e.g., Ro 14-4513] or that functionally antagonize diazepam at other sites on the GABA A receptor complex (e.g., pentylenetetrazol; Gerak and France, 1999). The similar although not identical binding profile of ␤-CCt and flumazenil at BZ receptors suggests that ␤-CCt antagonizes chronic diazepam at BZ receptors to precipitate withdrawal (Huang et al, 2000). ␤-CCt is approximately 100-fold less potent than flumazenil in diazepam-treated monkeys, a difference com- parable with that observed in untreated monkeys (see below; Paronis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…BZs such as diazepam and midazolam are nonselective (Huang et al, 2000), whereas non-BZ compounds such as zaleplon and zolpidem are approximately 10-fold selective for BZ 1 receptors compared with other GABA A receptors in binding assays in vitro (Dä mgen and Lü ddens, 1999;Huang et al, 2000). Selectivity at BZ 1 receptors might be responsible for zaleplon and zolpidem having behavioral effects that differ from those of nonselective BZs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, bCCt exhibits the greatest binding selectivity of the currently available a1 receptor ligands McKernan et al, 2000;Cox et al, 1998). In contrast, flumazenil is a nonselective BDZbinding antagonist at the diazepam-sensitive sites (Huang et al, 2000). In relation to physiological efficacy (ie, potentiation of GABAergic activity), Xenopus oocyte studies have reported that both bCCt and flumazenil demonstrate a neutral or low efficacy agonist response profile across the a1, a2, a3, a4, and a5 receptors .…”
Section: Hypothesized Mechanism Of Action In Reducing Etoh and Sucrosmentioning
confidence: 99%
“…A novel approach to achieve this goal was developed by Cook and coworkers in the 1980s (1,25) that employed a pharmacophore/receptor model based on the binding affinity of rigid ligands to BDZ/GABA A receptor sites (8). From this series of receptor models for ␣ 1-6 ␤3␥2 subtypes a robust pharmacophore for ␣5-subtype selective ligands emerged resulting in the synthesis of a novel ␣5␤3␥2 partial agonist modulator: (R)-ethyl 8-ethynyl-6-(2-fluorophenyl)-4-methyl-4H-benzo[f]imidazo [1,5-a] [1,4]diazepine-3-carboxylate (or SH-053-2=-F-R-CH 3 ) (10).…”
mentioning
confidence: 99%